HUBUNGAN ANTARA MOTIVASI MENJADI PERAWAT DENGAN PRESTASI BELAJAR MAHASISWA AKADEMI KEPERAWATAN WILLIAM BOOTH SURABAYA - ., YOSEPH K.E, LINA M (S1 Keperawatan, 2012)
Motivation is all verbal, physical, or psychological make someone do something in response. High motivation lead to viable businesses that have an impact on learning achievement of good. The purpose of this study was to find a relationship between motivation to become nurses with student learning achievement William Booth College of Nursing Surabaya. The design of this study using a correlation method. Sampling is used Simple Random Sampling. Samples taken as many as 92 respondents. The selection of researchers into the percentage of respondents divided by the number of students per class as a whole. Way of sampling the NIM respondents wrote in the paper and then rolled up and then collected by each force and then pick it up at random. Data research on motivation and learning achievement is taken by using a questionnaire and achievement documentation of student. After the data were tabulated and analyzed to see the relationship between motivation to become nurses with learning achievement. The results showed that students have high motivation to become nurses as many as 17 people (18.48%), while as many as 53 people (57.61%), and low total of 22 people (23.91%). Learning achievements obtained by the laudable achievements of learning as much as 7 people (7.60%), very satisfying as many as 39 people (42.40%), satisfying as many as 32 people (34.78%), just as many as 8 people (8.70% ), and do not pass as many as 6 people (6.52%). Based on assay results cross tabulation be obtained there is a relationship between motivation become nurse with achievement learn the student. Seeing the results of this study then the need to be the existence of good support from family, lecturers, and institutions to enhance the motivation college students in order be able to achievement learn to them good.Keywords: Motivation, learning achievement